Exploring Integrated Writing Task (Reading-Listening-Writing) In Toefl IBT - Tiara Kristina Pasaribu; Donna Ria Pasaribu; Sondang Manik; Desta Lenta Hawa; Nopriyanti Octavia Simbolon (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to explore university students’ abilities in completing the Integrated Writing Task of the TOEFL IBT, which requires the integration of reading, listening, and writing skills. The TOEFL is a standardized assessment designed to evaluate proficiency in Listening, Structure, Reading, and Writing. Within the TOEFL iBT format, the Writing section differs significantly from the PBT and CBT versions because test-takers must synthesize information from a reading passage and a related academic lecture. They are expected to explain the relationship between the two sources—whether similarities, differences, or contrasting viewpoints—and present the information in a coherent written response. As learners of English as a Foreign Language (EFL), students may experience various difficulties throughout this process. These challenges may include recognizing sounds, understanding the meaning of words and phrases, interpreting paragraphs, and accurately transcribing information from spoken texts. Therefore, this research focuses on two main questions: (1) What challenges do students face in reading and listening while completing the Integrated Writing Task of the TOEFL IBT? and (2) What types of mistakes do students make in their written responses for the integrated task? The novelty of this study lies in its focus on EFL students in North Sumatra who have never taken the TOEFL IBT. Thus, the research provides empirical insight into how these students comprehend, process, and integrate information across language skills. The findings are expected to contribute to the development of more effective English language teaching strategies, particularly in developing curriculum to include integrating Reading, Listening, Writing skills. It also aimed imo preparing students for the demands of the TOEFL IBT.